Analisa Kenyamanan Kendaraan Multiguna Pedesaan Pada Kekasaran Jalan Iso 8608 - Nanda Pranandita (Politeknik Manufaktur Negeri Bangka Belitung, 2016)
The vehicle suspension system is an important part to minimize the vibration of the vehicle caused by road unevenness. The classification of the road surface in this study is based on the classification of road roughness